Vilfredo Pareto: la «deformazione» della democrazia - Della Pelle, Piergiorgio (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2024)
When Vilfredo Pareto wrote the articles composing “The Transformation of Democracy” (1921) the Western world was sapped by World War I and still feeling the echo of the Russian October Revolution of 1917. Specifically, in Italy, the events of the “Biennio Rosso” (the Two Red Years – 1919-1920) seemed to clarify even further for Pareto that democracy did not have a unique form but was subject to evolution. Reading this book, 100 years after its publication, in the light of Pareto’s theory of society, with particular reference to the “circulation of élites” and the relationship between facts and theories (drawing attention to his connection with the young Benedetto Croce), it is possible to understand the real meaning of his reference to a “demagogic plutocracy”. This is a political and social concept that even now could be used to read the contemporary world. Democracy; Élites; Transformation; Pareto; Croce.